Improvement of drying process in fish cracker production - Shazmier Shah, Dilbar Shah (2013)
Fish cracker industry is one of the products from fish processing industry which is included in East Coast Economic Region (ECER). This project is focused on the productivity improvement in fish cracker processing, specifically of the drying process. Drying process involves process of removing water from the fish cracker from boiling stage. This project is proposed as an alternative to workstation rearrangement and also introduces better technology into this small medium industry. Currently, fish cracker is dried under the sun for few hours or put in drying compartment for 1 to 2hours. This study is proposed to develop better performance drying system with lower energy consumption and higher heating efficiency. In order to make this project happen, there are few things need to be considered, first the hygiene aspect, drying time, space, quality and ergonomic value. This research is based on the observation of a small fish cracker factory at Tanjung Lumpur, Kilang Keropok Mak Teh which already runs around 33 years. Most of the equipment at the factory are outdated and need to improve so that the productivity of the factory could be increase. Drying process is one of the workstation that consume most of the time, so if the drying time can be decrease, the productivity can be increase. Based on the objtive of this rojet, the new design of the drying system has been done. The analysis using numerical method software ANSYS (CFX) shows how the heat distributed inside the drying system and the air flow inside it